A 5Gbit/s CMOS clock and data recovery circuit - Sulaiman , Mohd Shahiman; Mohd-Yasin, F; Reaz, Mamun B. I.; Soon-Hwei, Tan; Kok-Siang, Tan (2005)
This paper presents a half-rate 5Gb/s clock and data recovery circuit. Retiming of data is done by the linear PD that provides practically no systematic offset for the frequency band of interest The circuit was designed in a 0.18-mu m CMOS process and occupies an active area of 0.2 x 0.32 mm(2). The CDR exhibits an RMS jitter of +/- 1.2 ps and a peak-to-peak jitter of 5ps. The power dissipation is 97mW from a 1.8-V supply.